Monetary policy and balance sheet adjustment - Otmar Issing (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
In the wake of the Global Financial Crisis that started in 2007, policymakers were forced to respond quickly and forcefully to a recession caused not by short-term factors, but rather by an over-accumulation of debt by sovereigns, banks, and households: a so-called balance sheet recession. Though the nature of the crisis was understood relatively early on, policy prescriptions for how to deal with its consequences have continued to diverge. This paper gives a short overview of the prescriptions, the remaining challenges and key lessons for monetary policy.
urn:nbn:de:hebis:30:3-343256
Keywords: 330; recession; monetary policy; balance sheet adjustment